2020
DOI: 10.1111/ped.14192
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia cutis congenita in Korea: Single center experience and literature review

Abstract: Background Aplasia cutis congenita (ACC) is a rare congenital malformation characterized by a localized absence of skin. which most commonly affects the scalp. We performed the present study to elucidate the basic clinical data regarding ACC in Korea, including demographics, clinical features, radiological and therapeutic results. Methods Fifty‐nine patients (70 lesions) with ACC (35 from our department and 24 from a Koreamed database search) were enrolled. We assessed demographics, family and obstetrical hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The male‐to‐female ratio was greater than 1 in our study, in line with what is commonly reported in the literature 5,25 . We found that the scalp was the most common site for ACC and more frequent (96.4%) than reported by Frieden (86.0%), 3 Sathishkumar et al 5 (82.1%), and Mesrati et al 4 (72.7%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The male‐to‐female ratio was greater than 1 in our study, in line with what is commonly reported in the literature 5,25 . We found that the scalp was the most common site for ACC and more frequent (96.4%) than reported by Frieden (86.0%), 3 Sathishkumar et al 5 (82.1%), and Mesrati et al 4 (72.7%).…”
Section: Discussionsupporting
confidence: 92%
“…Given the rarity of the condition, most information about ACC exists as individual case reports and in some medium‐sized studies 3–5,18–25 …”
Section: Introductionmentioning
confidence: 99%
“…Aplasia cutis congenita is a rare congenital malformation characterized by localized or widespread defects or scarring of the skin at birth. In more severe cases, bone defects can be detected 1 . Although several theories have been proposed as to its pathogenesis, incomplete closure of the neural tube may explain midline lesions of ACC 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The woman reported to have no exposure to known aetiological factors. 5 , 6 , 7 Given causal relationship has been established between viral infection and ACC, for example, human immunodeficiency virus, varicella zoster virus and herpes simplex virus; 5 , 6 , 7 the maternal SARS‐CoV‐2 infection may cause the ACC in the neonate.…”
Section: Figurementioning
confidence: 99%